A Spanish sunrise : a novel - Walker, Boo (Lake Union Publishing, 2022)
"Adjusting to the death of his wife hasn't been easy on Baxter Shaw--or on their eight-year-old daughter, Mia. Baxter has left his band and abandoned his dreams to focus on being a single father, but it's not enough: Mia's exhibiting escalating behavioral problems. And neither has been able to face the past head-on...until the past reaches out to them. After surprising results from a DNA test, Baxter and Mia journey to southeastern Spain to connect with their mysterious roots. Staying in a centuries-old villa on a renowned olive oil estate, they come to know the family they never realized they had, including a woman whose strength and passion for the estate remind Baxter of the love he lost--and that it's not too late to rekindle his own dreams. For Baxter and Mia, it's a healing season in Spain, and the romance of the culture awakens a new outlook on life. But when long-simmering family secrets surface and the estate's fate is called into question, Baxter must choose to let go of the past if he ever hopes to find love and live again."--Back cover.